Two new cryptic species of the Cyrtodactylus irregularis complex (Squamata: Gekkonidae) from southern Vietnam - Nazarov, Roman; Poyarkov, Nikolay A.; Orlov, Nikolai L.; Phung, Trung My; Nguyen, Tao Thien; Hoang, Duc Minh; Ziegler, Thomas (Zootaxa, 2012)
We describe two new species of the Cyrtodactylus irregularis complex both based on phylogenetic analysis of 654 bp of COImtDNA gene and morphological analyses of voucher specimens from Binh Phuoc and Lam Dong provinces, southern Vietnam.Cyrtodactylus bugiamapensis sp. nov. is described from the monsoon tropical forests of Bu Gia Map National Park, BinhPhuoc Province, and is distinguished from the remaining representatives of the C. irregularis complex by a combination of thefollowing characters: (1) size medium, with a maximum SVL of 76.8 mm; (2) original tail relatively thin, longer than body; (3)presence of enlarged femoral scales without femoral pores; (4) preclocal groove lacking; (5) 36–46 longitudinal rows of ventralscales at midbody; (6) males with 7–11 precloacal pores in an angular continuous series; (7) absence of enlarged subcaudals;(8) dorsal pattern consisting of a dark neck band which can be medially divided, and irregular dark brown spots with brightwhite edges. Cyrtodactylus bidoupimontis sp. nov. is described from mountainous evergreen tropical forests of Bidoup – NuiBa National Park, Lam Dong Province, and is most similar to C. irregularis sensu stricto from which it is distinguished by acombination of the following characters: (1) absence of enlarged, strongly keeled conical tubercles on the dorsal tail-base; (2)presence of flat rounded smooth to weakly keeled dorsal tubercles; (3) pallid dorsal head surface pattern lacking distinct darkbrown irregular spots with light edges; and (4) elongated limbs. Phylogenetic analyses revealed the presence of a number ofcryptic allopatric species within the C. irregularis complex. Long geological history and complicated relief of the Lang Bianplateau and surrounding areas might have shaped the present diversity within the C. irregularis complex. COI DNA-barcoding appears to be a useful tool to reveal cryptic diversity within the genus Cyrtodactylus.